Antibacterial, and antioxidant potentials of non-cytotoxic extract of Trichoderma atroviride. (February 2018) - Saravanakumar, Kandasamy; Chelliah, Ramachandran; Ramakrishnan, Sudha Rani; Kathiresan, Kandasamy; Oh, Deog-Hwan; Wang, Myeong-Hyeon
Abstract: Trichoderma species are a rich source of metabolites, but less known for biomedical potential. This work deals with antibacterial and antioxidant potentials of intracellular non-cytotoxic metabolites, extracted from Trichoderma atroviride (KNUP001). A total of 53 fractions was collected by column chromatography and tested for cytotoxicity by MTT assay. Only one fraction (F41) was found to be non-toxic to Vero cells with 95.4 ± 0.61% of survival. The F41 was then subjected to chemical analysis, antibacterial and antioxidant assays. The F41 at 500 μg ml −1 showed the total antioxidant of 48.70 ± 2.90%, DPPH radical scavenging activity of 37.25 ± 2.25, nitric oxide (NO) radical scavenging activity of 54.55 ± 1.95 and H2 O2 radical scavenging activity of 43.75 ± 3.21. The F41 at 25 μg ml −1 displayed antibacterial activity against E. coli (14.25 ± 0.25 mm), Proteus mirabilis (10.40 ± 0.60 mm), and Enterobacter aerogenes (5.60 ± 0.40 mm). GC-MS analysis revealed the dominant presence of oleic acid C 18.1 (63.18%), n-hexadecanoic acid (6.17%), and ethyl oleate (4.93%) in the F41, and hence these fatty acids are likely responsible for the antioxidant and antibacterial activities of F41. Hence, further investigation deserves on purification and characterization of the active metabolites from T. atroviride strain KNUP001 towards developing molecular leads to effective antibacterial drugs, and non-toxic to host cells. Graphical abstract: Image 1 Highlights: Non-cytotoxic metabolites extracted from Trichoderma atroviride . Potential antibacterial and antioxidant activity credited to the synergic effect of non-cytotoxic metabolites. Fatty acids, oleic acid C 18.1, n-hexadecanoic acid, and ethyl oleate are the dominant presence in non-cytotoxic metabolites.